Financial Implications of the Urban-rural Divide - Mori, Margherita (Current Aspects in Business, Economics and Finance Vol. 5, 2022)
This chapter aims to provide a conceptual framework for analysing financial issues related to population imbalances, which result from a long-standing trade-off between rural and urban communities. The significant differences in their intrinsic characteristics lead to evoke a wide gap in terms of financial inclusion, emphasising the importance of finance. Technological advances that continue to stimulate progress in the financial industry, particularly in the delivery of financial services, and that fuel optimism about digitization as a catalyst for mitigating the polarisation under scrutiny are among the factors to be investigated. Findings sketch on best practises and success stories involving ag(ri)tech and fintech that are worth disseminating and sharing in order to contribute to the post-pandemic "new normal" as a prerequisite for the anticipated "new future."